The Gospel of Mark's Judaism and the death of Christ as ransom for many - VanMaaren, John (Wissenschaftliche Untersuchungen zum Neuen Testament, 2025)
In this book, John Van Maaren argues that viewing the Gospel of Mark as an expression of first-century Judaism – rather than post-Jewish, Gentile Christianity – offers a more coherent reading of the narrative while illuminating its unique features.